Preparation and Synthesis of Activated Carbon From Areca Nut Shell Coated with Nanochitosan From Shrimp Shell - Herlinawati Herlinawati; Qisthina Fildzah; Junifa Layla Sihombing; Agus Kembaren (Universitas Syiah Kuala, 2025)
This study aims to determine the manufacture of adsorbents made from activated carbon areca nut shell coated with nanochitosan from shrimp shells. The carbon from the areca nut shell was obtained by heating process using a temperature of 300oC. The carbon obtained is activated with H2SO4 and then modified by coating activated carbon with nanochitosan. Chitosan was prepare through isolation the stages of deproteinization, demineralization, and deacetylation. Chitosan will be characterized using FTIR. The change in size of chitosan to nano chitosan was evaluated by ionic gelation method with 1% NaTPP. The nanochitosan obtained will be characterized using PSA. The results of FTIR characterization showed the presence of an N-H group at a wave number of 3345.89 cm-1. PSA characterization gave a result that the particle size of shrimp shell chitosan was nano-sized, which was 51.11 nm.